Knowledge of Employed Mothers and Housewives Toward Family Physicians in Primary Health Care Centers - Salih Ismael, Nibras; Hussein Kadhim, Shahad (South Asian Journal of Social Sciences and Humanities, 2025)
Background: Family physicians play an essential role and act as a communicational bridge between people and the healthcare system in providing healthcare services efficiently. Aim of study: To evaluate the Knowledge of Employed mothers and housewives toward family physicians in primary health centers and to identify the general satisfaction of participants with the services provided by Family physicians. Methodology: A cross-sectional study was conducted in 4 primary health care centers in Baghdad (AL-Resafah sector, AL-Karikh sector), from 1st of January 2019, to 1st of June 2019. Sample of a study from a mother who attended the PHCC, who has multiple visits. Result: 72.8% were living in an urban area and the rest 27.2% were from rural areas. Educational level categorized into primary and less, secondary, and institution, college, above with 65(26%), 133(53%), 52(20.8%), respectively. Nearly half of the participants were employed, 112(44.8%) of participants prefer physicians’ age≥45y, 128(51.2%) of participants have no difference for preferring physicians’ gender. 141(56.4%), 140(56%) of participants didn’t know that the PHC doctors are family physicians and didn’t know that the family physicians are specialists, respectively. Conclusion: More than half of the participants have good Knowledge of family physicians. There was no statistically significant difference in some of the participants’ characteristics and satisfaction level. Some of the participants showed dissatisfaction with the appointment for the next visit, and more than half showed dissatisfaction with the waiting time. The results showed that the knowledge of Employed mothers was better than the knowledge of housewives.